2019
DOI: 10.1080/1331677x.2018.1555048
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency comparison of unit and ad valorem taxation in mixed duopoly

Abstract: In this paper, we consider the relative efficiency of unit taxation and ad valorem taxation in terms of welfare implications in different imperfectly competitive markets. Under the assumption that these two taxations can produce the same total output in equilibrium, which is also used by Anderson (2001), we show that ad valorem taxation is always welfare superior to unit taxation under full nationalisation, full privatisation, and partial privatisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The environmental tax payment paid by firm i after ER&D is: T i ¼ tð1Àr i Þq i , where t stands for the tax rate (t>0). 8 It is worth noting that Tao et al (2019) compare the efficiency of unit and ad valorem taxation in the mixed duopoly. The profit function for firm i can be expressed as:…”
Section: The Modelmentioning
confidence: 99%
“…The environmental tax payment paid by firm i after ER&D is: T i ¼ tð1Àr i Þq i , where t stands for the tax rate (t>0). 8 It is worth noting that Tao et al (2019) compare the efficiency of unit and ad valorem taxation in the mixed duopoly. The profit function for firm i can be expressed as:…”
Section: The Modelmentioning
confidence: 99%
“…Of note, Mujumdar and Pal (1998) and Tao et al. (2019) demonstrated that an ad valorem tax is welfare superior to a specific tax. Considering the shadow cost of public funds, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, an increasing number of studies are exploring privatization and trade policies in an international mixed oligopoly market, but only Mujumdar and Pal (1998), Tao et al (2019), and Zhang et al (2020) compared an ad valorem tax and a specific tax in a closed economy. Of note, Mujumdar and Pal (1998) and Tao et al (2019) demonstrated that an ad valorem tax is welfare superior to a specific tax. Considering the shadow cost of public funds, Zhang et al (2020) reported that if the privatization level is low (medium, high), the government must adopt ad valorem (specific, ad valorem) tax.…”
mentioning
confidence: 99%
See 1 more Smart Citation